ANTIBACTERIAL SCREENING OF THE CULTURE OF ENDOPHYTIC FUNGAL EXTRACTS ISOLATED FROM CINNAMON STICK (Cinnamomum burmannii [Nees & T. Nees] Blume) - Praptiwi, -; Ilyas, Muhammad; Wulansari, Dewi; Agusta, Andria (LIPI Press, 2015)
Pathogenic bacterial resistance to antibacterial agents used in the treatment of recent formal systems have undergone significant increase. It is necessary to get a source of new antibacterial agents to overcome resistance. Endophytic fungi have been known as one of the organisms that have the ability to produce a variety of bioactive metabolites. In this study, 26 endophytic fungi have been isolated from various parts of Cinnamomum burmannii plant. The results of antibacterial activity screening of endophytic fungal extracts byTLC bioautography method without elution showed that as many as 18 extracts inhibited the growth of Staphylococcus aureus InaCC-B4 with the diameter of inhibition zone (DIZ) were in the range of 5.00 to 16.00 mm. On the other hand, the number of extracts that could inhibit the growth of Escherichia coli InaCC-B5 were 24 extracts with the DIZ were in the range of 4.00 to 28.00 mm. A detailed analysis of eluted TLC-bioautography method showed the chemical compounds of extracts that were responsible for antibacterial activity.